Avaliação microscópica de implante de polietileno poroso de alta densidade utilizado em processo alveolar - Oliveira, Renato Victor de (2009)
The lost of one or more teeth leads to damage of alveolar process due to the varying degrees of bone resorption, depending on the causes or the affected region. Maxilla is especially susceptible to resorption, mainly in the anterior region for its bone characteristics. For local rehabilitation, autogenous bone grafts are usually employed, favoring dental implants insertion, connective tissue grafts for aesthetics purposes, or even prosthetic adaptation. For aesthetic purposes, other materials are being tried, as the high density porous polyethylene (HDPP), especially when filling and contouring of some regions such as chin and zygoma are desired. The present study suggested the use of HDPP in alveolar process as an alternative to autogenous grafts and prosthetic devices. For this, New Zealand rabbits underwent surgical procedure to receive HDPP onlay implants in buccal face of mandibular alveolar process, fixed with titanium screws. After 7, 15, 45, and 90 days, the animals were killed and the specimens retrieved for histological and imunohistochemical analysis. No implant loss or infection was detected at the retrieval of the specimens. The microscopical analysis presented sactisfatory integration of the material to the bone surface, with new bone formation in the receptor bed and inside the pores of the material, observed from the 45th day. Imunohistochemistry showed low expression of Cbfa-1 and moderate of VEGF at all observed periods. These results encourage the indication of use of HDPP in alveolar ridge when aesthetic recovery is needed.